Rediscovering the Child: Review of Montessori Action Research Studies 2022—2023 - Carver , Kateri; Hassebroek , Sarah (Journal of Montessori Research, 2023)
Action research is the term used for investigations done in the field, often by practitioners, and typically with a pragmatic rather than theoretical purpose (Willis & Edwards, 2014). This type of research is a key part of many Montessori teacher education programs, but the value of this important work is often lost to the field because the papers reside in separate institutional repositories with limited indexing. The Journal of Montessori Research is introducing a new annual review article series which features selected graduate student action research studies. The authors of this recurring series of articles represent Montessori teacher preparation programs and other university-based research roles. They will select studies that they believe are particularly high quality and relevant to the journal’s readers. We are calling this series of articles “Rediscovering the Child” to honor Maria Montessori’s seminal work and to acknowledge that all Montessori teachers engage in an ongoing process of rediscovering the children in their classrooms. When this process is formalized, action research is the result. This article is the first in the series and highlights six studies from University of Wisconsin-River Falls and St. Catherine University. In the coming issues, we will likely refine some aspects of our selection and review processes and expand the programs represented.